ENZYMATIC ACTIVITY OF TYPICAL BLACK SOIL DEPENDING ON THE MAIN CULTIVATION OF SOIL AND FERTILIZER - Центило, Л. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
All agrotechnical and agrochemical measures aimed at increasing soil fertility have an effect on enzyme activity. Measures such as soil cultivation, the introduction of organic and mineral fertilizers into the soil,activate or suppress the enzymatic processes. The research relies on the intensity and direction of biochemical processes in the soil, containing a series of methods, the use of which has enabled the establishment of a favorable enzymatic active layer of arable chernozem typical. Such methods include: field, laboratory, analysis. The level of differentiation of protease, urease, phosphatase, amylase, catalase, depending on the cultivation of soil and fertilizer, was revealed in the process of comparative analysis of enzymic activity of typical black soil in sunflower agrocenosis. Field experiments on the study of fermentative activity of typical black currant were conducted during 2012-2016. The object of research was soil cover. It was established that the activation of biochemical processes in the soil is ensured by the organo-mineral fertilizer system - compost 4.5 t + N40P48K54 + 3.5 t by-products and seed weight per hectare of crop rotational area. Application of the mineral fertilizer system reduces the enzymatic activity of typical black soil. The highest activity of the protease and catalase passes in the arable layer for powered-unpowered cultivation. Higher phosphatase activity was observed for differentiated soil cultivation. Research on this problem should be continued in order to establish a relationship between the parameters of enzymatic activity of soil with the structure of microbial cenosis of typical black soil of different systems of basic cultivation and fertilization